Diversity of Anaerobic Methane Oxidizers in the Cold Seep Sediments of the Okinawa Trough - Chen, Ye; Xu, Cuiling; Wu, Nengyou; Sun, Zhilei; Liu, Changling; Zhen, Yu; Xin, Youzhi; Zhang, Xilin; Geng, Wei; Cao, Hong; Zhai, Bin; Li, Jing; et al. (Frontiers in Microbiology, 2022)
Active cold seeps in the Okinawa Trough (OT) have been widely identified, but the sedimentary microbial communities associated with cold seeps are still poorly understood. Here, we investigated the distribution and biomass of microbial community, particularly the microbes involved in methane metabolism, from sediments of an active cold seep in the mid-Okinawa Trough. Methane-oxidizing archaea, including ANME-1a, ANME-1b, ANME-2a/b, ANME-2c and ANME-3, and methanogen, including Methanofastidiosales and Methanomassiliicoccales were detected at the OT cold seep sediments. A vertical stratification of dominating ANME communities was observed in the following order: ANME-3, ANME-1a and ANME-1b. In addition, we found that the mcrA gene and ANME-1 16S rRNA gene copy numbers were specifically higher at the peak of dissolved iron, suggesting that methane-metabolizing archaea might participate in iron reduction coupled to methane oxidation (Fe-AOM) in the OT cold seep. Furthermore, the relative sequence abundance of ANME-1a was strongly related to the concentration of dissolved iron, indicating that ANME-1a was a microbial key player for Fe-AOM in the OT cold seep sediments. Co-occurrence analysis revealed that methane-metabolizing microbial communities were mainly associated with heterotrophic microorganisms such as JS1, Bathy-1 and Bathy-15, illustrating a synergistic effect between methane metabolism and organic matter degradation.